The health hump - Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
In this paper, I suggest a novel explanation for a hump-shaped ageconsumption profile, based on human aging. The model integrates health in the utility function and utilizes recent estimates on the effects of health on the marginal utility of consumption. The parsimonious model has a closed-form solution for the age of peak consumption and the consumption level at that age relative to initial consumption. A calibration of the model with data from gerontology produces an empirically plausible hump in consumption.
Keywords: D91; E21; I10; 330; health; aging; life-cycle consumption